Functional and Semantic Extension of the Sentence of the Modern Ukrainian Literary Language - Oleksii Vorobets (Vasyl Stefanyk Precarpathian National University, 2022)
The latest linguistic research has witnessed a strengthening of the analytical consideration of syntactic semantics, the introduction of functional-semantic approach to determining the specifics of the sentence, its nucleus and potentially nucleus components in the inter-categorical section. It is obvious that the analysis of the sentence semantic organization takes into consideration the functions of individual syntaxemes, their system relations network, as well as syntactic properties of grammatical classes of words. At the same time, there arises a problem of complex analysis and interpretation of the mechanisms of semantics and functioning of a syntactic organization in general, as well as each of its units in particular. Typology of the syntactic system of the Ukrainian language, introduction of changes into the "from semantics to function", "from function to semantics", "complex, semantic and functional potential" ideas, all these contribute to the study of syntactic constructions on both the superficial and deep meaning levels. It is noteworthy that linguistic semantics relies on the idea of ​​"non-alternative picture of the world" that is a generalized picture of a one-dimensional type, which excludes the option of complementary and mutually contradictory procedures in its interpretation.  Singling out of the extenders in the syntactic plane is connected to the extending way of thinking of the individual, which provides a defining conceptual background of scientific developments, acting as a tool for understanding reality in general and the extending basis of sentence construction in particular. It is the extended view of the surrounding reality allows interpreting the branched system of semantic components and meanings in various structural syntactic units. Given that the sentence, its structure, responsible for the unity of both the superficial and deep meaning, is the sphere of functioning of syntactically tuned elements, and, therefore, a multifaceted unit allowing interaction of formal, semantic and syntactic features of sentence entities, it is the multifaceted nature of a sentence that provides the context for extenders study. Functional-semantic extension of the sentence consists of a four-component hierarchy of extender models: elementary extender; extender complex; extender system; mega- extender, and that indicates the semantic potential of the studied syntactic units both from the standpoint of potentially main / main predication, and in terms of functioning in a framework of simple and complex sentences. The study of the problem is complemented by transformational intentions of the extending components, and it allows reaching to the deep meaning of the sentence through functional-semantic features.